Pengaruh Komitmen Organisasi Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Dengan Pemoderasi Lean Management di CV Aji Soko Abadi - Muhammad Bahril Ilmiddaviq (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
The quality of financial reports is an indicator in determining the existence of good business management. The good and bad of the company can be reflected in the existence of quality financial reports. The existence of differences in research that has been done motivates researchers to conduct development research using lean management as a moderating variable. This study uses regression analysis using path analysis. The results of this study indicate that there is a partial or simultaneous influence of Organizational Commitment and Human Resource Competence on the Quality of Financial Statements. In addition, the data processing carried out shows that the lean management variable is able to moderate the overall effect of organizational commitment and HR capacity on the quality of financial reports.